MIGRATION POLICY OF THE RUSSIAN FEDERATION - Yugova, Ksenia; Kotýnková, Magdalena, 1948-; Říhová, Vladimíra; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
The Master's thesis investigates a range of problems of migration policy of the Russian Federation. The main goal of the thesis is to identify causes, that underlay inefficiency of implemented measures in migration field; and to develop recommendations to make the Russian migration policy more efficient. A work solution process is based on the hypothesis that goals and tools of the Russian migration policy are not enough consecutive and effective, therefore the whole system requires revision and alteration. The theoretical part discloses the impact of migration on a national economy and provides considerations about how to create an efficient migration policy. The practical part focuses on analysis of Russian immigration, emigration and internal-migration policies. This part completes with author's proposals how to improve Russian migration policy. Research is conducted using the method of description, relation and qualitative analysis and prediction method.
Vedoucí práce: Magdalena Kotýnková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses